A Spectrum of Inclusion: Climate and Environmental Justice Teaching in a Technical Context - Christopher Rabe; Madeline Schlegel; Julia Reich; Ashanti Mclean; Olivia Girand; Claire Webster; Sabrina Araujo-Elorza (Journal of Environmental Studies and Sciences, 2026)
Although a substantial body of research has examined how sustainability is integrated into higher education curricula, relatively few studies have explored how instructors incorporate climate and environmental justice (CEJ) content and pedagogies across disciplines. Emerging scholarship has begun to address how interdisciplinary environmental and sustainability (IES) programs and institutional sustainability requirements include environmental justice (EJ) course content. Yet when CEJ knowledge is not broadly embedded across disciplines by IES faculty or institutional leaders, the resulting curricular gaps often exclude the content, practices, and lived experiences of those most affected by global environmental and climate challenges. This exclusion, especially common in STEM-focused areas, can have significant consequences for underrepresented students. This study investigates these dynamics within a STEM institutional context, examining how faculty and instructors incorporated CEJ content and pedagogy across 11 courses at a four-year, private, technical institution. Using a case-study approach and multiple data sources, the study identifies four clusters within a spectrum of CEJ inclusion, each characterized by distinct experiential pedagogies such as community engagement, transdisciplinary methods, and the use of diverse epistemologies. The findings also reveal that CEJ content was most often integrated into STEM courses through collaboration with the social sciences and humanities. Based on these results, the authors offer recommendations for instructors and campus leaders, including improving CEJ visibility in course catalogs, strengthening CEJ integration within STEM and computer science, expanding initiatives and training focused on community engagement, and formally recognizing the contributions of community partners through instructional titles.

High-resolution mapping and terrain classification of Halimeda bioherms in the northern Great Barrier Reef - Zsanett Szilagyi; Luke Nothdurft; Stephanie Duce; Jody M. Webster; Mardi McNeil; Robin J. Beaman; Juan Carlos Braga; Trevor Graham; Maria Byrne; Amy Nau; Christopher Berry; Victorien Paumard; et al. (Geomorphology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Are wildfire risk mitigators more prepared to evacuate? Insights from communities in the Western United States - Grant Webster; Hannah Brenkert-Smith; Patricia A. Champ; James R. Meldrum; Kelly Wallace; Colleen Donovan; Carolyn Wagner; Christopher M. Barth; Josh Kuehn; Suzanne Wittenbrink; Christine Taniguchi (Ecological Economics, 2025)

Wildfire risk information sources and the acceptability of fuels treatments near select WUI communities in the Western United States - Kelly Wallace; Hannah Brenkert-Smith; Patricia A. Champ; James R. Meldrum; Grant Webster; Christine Taniguchi; Julia B. Goolsby; Colleen Donovan; Carolyn Wagner; Christopher M. Barth; Josh Kuehn; Suzanne Wittenbrink (Forest Policy and Economics, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Characterizing northern white-cedar communities in harvested and unharvested lowland forests of Michigan, USA - Robin Michigiizhigookwe Clark; Christopher R. Webster; Laura S. Kenefic; Christel C. Kern; Rodney A. Chimner (Wetlands Ecology and Management, 2024)

What does climbing mean exactly? Assessing spatiotemporal gait characteristics of inclined locomotion in parrots - Melody W. Young; Clyde Webster; Daniel Tanis; Alissa F. Schurr; Christopher S. Hanna; Samantha K. Lynch; Aleksandra S. Ratkiewicz; Edwin Dickinson; Felix H. Kong; Michael C. Granatosky (Journal of Comparative Physiology A, 2024)

An experimental approach to identify drivers of tree regeneration diversity, composition, and heterogeneity in northern hardwood forests - Claudia I. Bartlick; Julia I. Burton; Christopher R. Webster; Robert E. Froese; Yvette L. Dickinson (Forest Ecology and Management, 2023)

Influence of silvicultural practices in northern hardwood forests on a long-lived perennial herb, Trillium cernuum L. - Christopher R. Webster; Julia I. Burton; Yvette L. Dickinson (Forest Ecology and Management, 2023)

Anthropogenic supply of nutrients in a wildlife reserve may compromise conservation success - Andrew J. Abraham; Ethan S. Duvall; Elizabeth le Roux; Andre Ganswindt; Marcus Clauss; Christopher E. Doughty; Andrea B. Webster (Biological Conservation, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Benthic micro‐ and macro‐community succession and coral recruitment under overfishing and nutrient enrichment - Nicolas R. Evensen; Inka Vanwonterghem; Christopher Doropoulos; Marine Gouezo; Emmanuelle S. Botté; Nicole S. Webster; Peter J. Mumby (Ecology, 2021)
Herbivory and nutrient availability are fundamental drivers of benthic community succession in shallow marine systems, including coral reefs. Despite the importance of early community succession for coral recruitment and recovery, studies characterizing the impact of top‐down and bottom‐up drivers on micro‐ and macrobenthic communities at scales relevant to coral recruitment are lacking. Here, a combination of tank and field experiments were used to assess the effects of herbivore exclusion and nutrient enrichment on micro‐ to macrobenthic community succession and subsequent coral recruitment success. Herbivore exclusion had the strongest effect on micro‐ and macrobenthic community succession, including a community shift toward copiotrophic and potentially opportunistic/pathogenic microorganisms, an increased cover of turf and macroalgae, and decreased cover of crustose coralline algae. Yet, when corals settled prior to the development of a macrobenthic community, rates of post‐settlement survival increased when herbivores were excluded, benefiting from the predation refugia provided by cages during their vulnerable early post‐settlement stage. Interestingly, survival on open tiles was negatively correlated with the relative abundance of the bacterial order Rhodobacterales , an opportunistic microbial group previously associated with stressed and diseased corals. Development of micro‐ and macrobenthic communities in the absence of herbivory, however, led to reduced coral settlement. In turn, there were no differences in post‐settlement survival between open and caged treatments for corals settled on tiles with established benthic communities. As a result, open tiles experienced marginally higher recruitment rates, driven primarily by the higher initial number of settlers on open tiles compared to caged tiles. Overall, we reveal that the primary interaction driving coral recruitment is the positive effect of herbivory in creating crustose coralline algae (CCA)‐dominated habitats, free of fleshy algae and associated opportunistic microbes, to enhance coral settlement. The negative direct and indirect impact of fish predation on newly settled corals was outweighed by the positive effect of herbivory on the initial rate of coral settlement. In turn, the addition of nutrients further altered benthic community succession in the absence of herbivory, reducing coral post‐settlement survival. However, the overall impact of nutrients on coral recruitment dynamics was minor relative to herbivory.

Differential and interacting impacts of invasive plants and white-tailed deer in eastern U.S. forests - David L. Gorchov; Bernd Blossey; Kristine M. Averill; Andrea Dávalos; J. Mason Heberling; Michael A. Jenkins; Susan Kalisz; William J. McShea; Janet A. Morrison; Victoria Nuzzo; Christopher R. Webster; Donald M. Waller (Biological Invasions, 2021)

Evidence for regional nitrogen stress on chlorophyll a in lakes across large landscape and climate gradients - Christopher T. Filstrup; Tyler Wagner; Samantha K. Oliver; Craig A. Stow; Katherine E. Webster; Emily H. Stanley; John A. Downing (Limnology and Oceanography, 2018)
Nitrogen (N) and phosphorus (P) commonly stimulate phytoplankton production in lakes, but recent observations from lakes from an agricultural region suggest that nitrate may have a subsidy‐stress effect on chlorophyll a (Chl a ). It is unclear, however, how generalizable this effect might be. Here, we analyzed a large water quality dataset of 2385 lakes spanning 60 regions across 17 states in the Northeastern and Midwestern U.S. to determine if N subsidy‐stress effects on phytoplankton are common and to identify regional landscape characteristics promoting N stress effects in lakes. We used a Bayesian hierarchical modeling framework to test our hypothesis that Chl a –total N (TN) threshold relationships would be common across the central agricultural region of the U.S. (“the Corn Belt”), where lake N and P concentrations are high. Data aggregated across all regions indicated that high TN concentrations had a negative effect on Chl a in lakes with concurrent high total P. This large‐scale pattern was driven by relationships within only a subset of regions, however. Eight regions were identified as having Chl a –TN threshold relationships, but only two of these regions located within the Corn Belt clearly demonstrated this subsidy‐stress relationship. N stress effects were not consistent across other intense agricultural regions, as we hypothesized. These findings suggest that interactions among regional land use and land cover, climate, and hydrogeology may be important in determining the synergistic conditions leading to N subsidy‐stress effects on lake phytoplankton.

Bird community responses to afforested eucalyptus plantations in the Argentine pampas - Colin C. Phifer; Jessie L. Knowlton; Christopher R. Webster; David J. Flaspohler; Julian A. Licata (Biodiversity and Conservation, 2017)

Prevalent and persistent viral infection in cultures of the coral algal endosymbiont Symbiodinium - Karen D. Weynberg; Matthew Neave; Peta L. Clode; Christian R. Voolstra; Christopher Brownlee; Patrick Laffy; Nicole S. Webster; Rachel A. Levin; Elisha M. Wood-Charlson; Madeleine J. H. van Oppen (Coral Reefs, 2017)

Global synthesis of the temperature sensitivity of leaf litter breakdown in streams and rivers - Jennifer J. Follstad Shah; John S. Kominoski; Marcelo Ardón; Walter K. Dodds; Mark O. Gessner; Natalie A. Griffiths; Charles P. Hawkins; Sherri L. Johnson; Antoine Lecerf; Carri J. LeRoy; David W. P. Manning; Amy D. Rosemond; et al. (Global Change Biology, 2017)
Streams and rivers are important conduits of terrestrially derived carbon (C) to atmospheric and marine reservoirs. Leaf litter breakdown rates are expected to increase as water temperatures rise in response to climate change. The magnitude of increase in breakdown rates is uncertain, given differences in litter quality and microbial and detritivore community responses to temperature, factors that can influence the apparent temperature sensitivity of breakdown and the relative proportion of C lost to the atmosphere vs. stored or transported downstream. Here, we synthesized 1025 records of litter breakdown in streams and rivers to quantify its temperature sensitivity, as measured by the activation energy ( E a , in eV ). Temperature sensitivity of litter breakdown varied among twelve plant genera for which E a could be calculated. Higher values of E a were correlated with lower‐quality litter, but these correlations were influenced by a single, N‐fixing genus ( Alnus ). E a values converged when genera were classified into three breakdown rate categories, potentially due to continual water availability in streams and rivers modulating the influence of leaf chemistry on breakdown. Across all data representing 85 plant genera, the E a was 0.34 ± 0.04 eV , or approximately half the value (0.65 eV ) predicted by metabolic theory. Our results indicate that average breakdown rates may increase by 5–21% with a 1–4 °C rise in water temperature, rather than a 10–45% increase expected, according to metabolic theory. Differential warming of tropical and temperate biomes could result in a similar proportional increase in breakdown rates, despite variation in E a values for these regions (0.75 ± 0.13 eV and 0.27 ± 0.05 eV, respectively). The relative proportions of gaseous C loss and organic matter transport downstream should not change with rising temperature given that E a values for breakdown mediated by microbes alone and microbes plus detritivores were similar at the global scale.

Artificial microtopography and herbivory protection facilitates wetland tree (Thuja occidentalis L.) survival and growth in created wetlands - Laura C. Kangas; Rose Schwartz; Michael R. Pennington; Christopher R. Webster; Rodney A. Chimner (New Forests, 2016)

Sharing rotting wood in the shade: ectomycorrhizal communities of co-occurringbirch and hemlock seedlings - Sarah K. Poznanovic; Erik A. Lilleskov; Christopher R. Webster (Mycorrhiza, 2015)

Effect of exercise intensity on post-exercise oxygen consumption and heart rate recovery - Theresa N. Mann; Christopher Webster; Robert P. Lamberts; Michael I. Lambert (European Journal of Applied Physiology, 2014)

A Migratory Ungulate Facilitates Cross-Boundary Nitrogen Transport in Forested Landscapes - Bryan D. Murray; Christopher R. Webster; Joseph K. Bump (Ecosystems, 2014)

Regional variability among nonlinear chlorophyll—phosphorus relationships in lakes - Christopher T. Filstrup; Tyler Wagner; Patricia A. Soranno; Emily H. Stanley; Craig A. Stow; Katherine E. Webster; John A. Downing (Limnology and Oceanography, 2014)
The relationship between chlorophyll a (Chl a ) and total phosphorus (TP) is a fundamental relationship in lakes that reflects multiple aspects of ecosystem function and is also used in the regulation and management of inland waters. The exact form of this relationship has substantial implications on its meaning and its use. We assembled a spatially extensive data set to examine whether nonlinear models are a better fit for Chl a —TP relationships than traditional log‐linear models, whether there were regional differences in the form of the relationships, and, if so, which regional factors were related to these differences. We analyzed a data set from 2105 temperate lakes across 35 ecoregions by fitting and comparing two different nonlinear models and one log‐linear model. The two nonlinear models fit the data better than the log‐linear model. In addition, the parameters for the best‐fitting model varied among regions: the maximum and lower Chl a asymptotes were positively and negatively related to percent regional pasture land use, respectively, and the rate at which chlorophyll increased with TP was negatively related to percent regional wetland cover. Lakes in regions with more pasture fields had higher maximum chlorophyll concentrations at high TP concentrations but lower minimum chlorophyll concentrations at low TP concentrations. Lakes in regions with less wetland cover showed a steeper Chl a —TP relationship than wetland‐rich regions. Interpretation of Chl a —TP relationships depends on regional differences, and theory and management based on a monolithic relationship may be inaccurate.

Broadening the ecological context of ungulate–ecosystem interactions: the importance of space, seasonality, and nitrogen - Bryan D. Murray; Christopher R. Webster; Joseph K. Bump (Ecology, 2013)
Spatial heterogeneity of soil resources, particularly nitrogen availability, affects herbaceous‐layer cover and diversity in temperate forest ecosystems. Current hypotheses predict that ungulate herbivores influence nitrogen availability at the stand scale, but how ungulates affect nitrogen availability at finer spatial scales that are relevant to the herb layer is less understood. We tested the hypothesis that ungulate exclusion reduces the spatial complexity of nitrogen availability at neighborhood scales (1–26 m) apart from mean stand scale effects. This outcome was expected due to a lack of ungulate nitrogenous waste deposition within exclosures and seasonally variable ungulate habitat use. To test this hypothesis we examined spatial patterning of ammonium and nitrate availability, herb‐layer cover and diversity, and under‐canopy solar radiation using geostatistical models. Our study sites included six stands of eastern hemlock ( Tsuga canadensis ) forest: three where white‐tailed deer ( Odocoileus virginianus ) were excluded and three that were accessible to deer. Where deer were present, patch sizes of ammonium availability, cover, and diversity were smaller compared to deer exclosures, whereas mean site‐level effects were not significant. Within deer exclosures cover and solar radiation were more similar in patch size than were cover and nitrogen availability. Our results suggest that browsing ungulates affect spatial patterns of herb‐layer cover and diversity through the excretion of nitrogenous wastes in small, discrete patches. Ungulate‐excreted nitrogen deposition and herbivory were concentrated in the dormant season, allowing herb‐layer plants a greater opportunity to benefit from nitrogen additions. Therefore, the impact of ungulates on nitrogen cycling in forest ecosystems varies with spatial scale and the seasonal timing of ungulate impacts. In this way, ungulates may function as a seasonally dependent link between fine‐scale and landscape‐level ecological processes.

Plantations for Bioenergy: Principles for Maintaining Biodiversity in Intensively Managed Forests - David J. Flaspohler; Christopher R. Webster (Forest Science, 2011)
As the value of forests for providing a feedstock for bioenergy increases, more land will probably be converted to fast-growing tree plantations to increase short-term production of cellulose. In general, plantations support fewer plant and animal species than native forests because plantations are greatly simplified in terms of tree and other plant species richness and in terms of many structural and process-related forest functions. However, native biodiversity can be retained in some plantation forests if careful management is used in all stages of plantation establishment, tending, and harvest. Key considerations for conserving biodiversity as plantation forests grow as a proportion of total world forest cover include choice of plantation tree species, harvest frequency, rotation age, and care and management of biological legacies and forest understory plant and wildlife communities. We provide background and guidance that can be used to guide future plantation management in a new era of using forests to capture and store carbon and to generate bioenergy.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Herbivore-induced expansion of generalist species as a driver of homogenization in post-disturbance plant communities - Stacie A. Holmes; Christopher R. Webster (Plant Ecology, 2011)

Bacterial Community Dynamics in the Marine Sponge Rhopaloeides odorabile Under In Situ and Ex Situ Cultivation - Nicole S. Webster; Rose E. Cobb; Rochelle Soo; Shelley L. Anthony; Christopher N. Battershill; Steve Whalan; Elizabeth Evans-Illidge (Marine Biotechnology, 2011)

Early Pennsylvanian, Bashkirian, echinoderms from eastern Iran, a potential transitional fauna between Laurentia/Avalonia and the Paleotethys, and a Permian cromyocrinid from central Iran - Gary D. Webster; Christopher G. Maples; Mehdi Yazdi; Sara Marcus; Johnny A. Waters (Palaeobiodiversity and Palaeoenvironments, 2011)

Promoting Ecological Sustainability in Woody Biomass Harvesting - Maria K. Janowiak; Christopher R. Webster (Journal of Forestry, 2010)
Enthusiasm for the use of forest biomass as an energy resource is growing as a result of increased energy costs and a desire to reduce the greenhouse gas emissions responsible for climate change. Although the opportunity exists for forests to have a significant role in the development and use of bioenergy technologies, justifiable concerns regarding the long-term sustainability of using forest-based energy feedstocks have emerged. In this article, we review the state of our knowledge regarding the impacts of intensive forestry with respect to issues relevant to bioenergy production, including soil and site productivity, hydrologic quality, and biodiversity. We then present guiding principles intended to aid with sustainable forest management decisions.

Ungulate Carcasses Perforate Ecological Filters and Create Biogeochemical Hotspots in Forest Herbaceous Layers Allowing Trees a Competitive Advantage - Joseph K. Bump; Christopher R. Webster; John A. Vucetich; Rolf O. Peterson; Joshua M. Shields; Matthew D. Powers (Ecosystems, 2009)

Age structure and spatial patterning of Trillium populations in old-growth forests - Christopher R. Webster; Michael A. Jenkins (Plant Ecology, 2008)

Spatial Scale and Stand Structure in Northern Hardwood Forests: Implications for Quantifying Diameter Distributions - Maria K. Janowiak; Linda M. Nagel; Christopher R. Webster (Forest Science, 2008)
Diameter distributions are frequently used to describe northern hardwood stand structure and serve as a structural guide for management. Several diameter distribution shapes have been found in managed and unmanaged uneven-aged northern hardwood stands, and it is unclear which patterns are due primarily to natural processes that could be self-perpetuating versus patterns that may be transient or aberrant. Variability in research methods has clouded consistent interpretation of resulting distributions. In this study, we evaluated northern hardwood stands in Michigan to determine how management and sample area affect interpretation of diameter distribution shape. Managed stands had a higher degree of variability in distribution shape and a tendency toward the increasing-q pattern. Unmanaged uneven-aged stands (i.e., old-growth remnants) were predominantly rotated sigmoid in shape. Patterns for each type of management became more consistent as sample area increased. Our data suggest a minimum sample area of 13% of total stand area may be needed to accurately capture diameter distribution shape; in this study that was 0.4 ha of a 3.2-ha sample plot. Additionally, greater heterogeneity in the structure of unmanaged stands resulted in the need for larger sample areas compared with that for managed stands.

Drought–herbivory interaction disrupts competitive displacement of native plants by Microstegium vimineum, 10-year results - Christopher R. Webster; Janet H. Rock; Robert E. Froese; Michael A. Jenkins (Oecologia, 2008)

Recruitment of Antarctic marine eukaryotes onto artificial surfaces - Nicole S. Webster; Christopher N. Battershill; Andrew P. Negri (Polar Biology, 2006)

Woody Invaders and the Challenges They Pose to Forest Ecosystems in the Eastern United States - Christopher R. Webster; Michael A. Jenkins; Shibu Jose (Journal of Forestry, 2006)
Invasive exotic species pose significant challenges for natural resource managers charged with the maintenance of biological diversity and the sustainable production of forest resources. In this article, we review what is known about the biology and control of some of the most serious woody invaders of eastern forests. Based on the parallels between these invasions, we propose a working framework for integrating invasive control into forestry practices. In general, early detection and rapid response to invasions are essential. However, given that consistently effective control strategies that are broadly applicable simply do not exist for many species, adaptive management strategies will be necessary.

Spatial Characteristics of the Invasion of Acer platanoides on a Temperate Forested Island - Steven R. Wangen; Christopher R. Webster; Jennifer A. Griggs (Biological Invasions, 2006)

Coarse Woody Debris in Managed Central Hardwood Forests of Indiana, USA - Michael A. Jenkins; Christopher R. Webster; George R. Parker; Martin A. Spetich (Forest Science, 2004)
We evaluated the volume of down deadwood (DDW) and the basal area of standing deadwood (SDW) from a chronosequence of 110 silvicultural openings and 34 mature stands (72–105 years old) across three Ecological Landtype Phases (ELTP; wet-mesic bottomlands, mesic slopes, and dry-mesic slopes) in southern Indiana, USA. The volume of DDW decreased with increasing opening age and was lower in clearcuts than in group-selection openings. Openings on mesic slopes and bottoms contained greater volumes of DDW than openings on dry-mesic slopes. Regardless of age and ELTP, openings contained low volumes of highly decayed DDW. The volume of small-diameter DDW decreased rapidly with increasing stand age across all three ELTPs. Mature stands contained low total volumes of DDW (maximum of 22.4 ± 5.1 m3 ha−1) and low volumes of both highly decayed and large-diameter DDW. Most of the dead trees in silvicultural openings were small diameter and did not contribute significantly to DDW volume. SDW basal area was very low in mature stands (maximum of 1.4 ± 0.5 m2 ha−1), suggesting that little mortality has occurred. Our results suggest that even and uneven-aged silviculture in hardwood forests have differing impacts on the volume and distribution of coarse woody debris (CWD). In addition, the mature stands that dominate forests across much of the Central Hardwood Region of the eastern United States contain relatively little CWD compared to younger and old-growth stands. FOR. SCI. 50(6):781–792.

Book reviews: Ecology and Control of Introduced Plants - Christopher R. Webster (Forest Science, 2004)
Intentional and unintentional introductions of exotic organisms have become commonplace in our increasingly global society. While many of these introductions have been benign, others have significantly altered native ecosystems and posed insurmountable challenges to agriculture, forestry, and the conservation of biological diversity worldwide.

Diverse microbial communities inhabit Antarctic sponges - Nicole S. Webster; Andrew P. Negri; Murray M. H. G. Munro; Christopher N. Battershill (Environmental Microbiology, 2004)
Summary Genetic techniques were employed to investigate the archaeal, bacterial and eukaryotic communities associated with the Antarctic sponges Kirkpatrickia varialosa , Latrunculia apicalis , Homaxinella balfourensis , Mycale acerata and Sphaerotylus antarcticus. The phylogenetic affiliation of sponge‐derived bacteria was assessed by 16S rRNA sequencing of cloned DNA fragments. Denaturing gradient gel electrophoresis (DGGE) was used to determine the stability of bacterial associations within each sponge species and across spatial scales. Of the 150 archaeal clones from L. apicalis , K. varialosa and M. acerata screened by restriction fragment length polymorphism (RFLP) analysis, four unique operational taxonomic units (OTUs) were observed and all clustered closely together within the Crenarchaeota . Of the 250 sponge‐derived bacterial clones screened by RFLP analysis, 61 were unique OTUs that were not detected during examination of 160 seawater‐derived clones. Rarefaction analysis indicated that the clone libraries represented between 44 and 83% of the total estimated diversity. Phylogenetic analysis of sequence data revealed that the bacterial communities present in Antarctic sponges primarily clustered within the Gamma and Alpha proteobacteria and the Cytophaga / Flavobacterium of Bacteroidetes group. Bacterial DGGE analysis for replicate sponge and seawater samples at each Antarctic site revealed that bacterial communities were consistently detected within a particular species regardless of the collection site, with six bacterial bands exclusively associated with a single sponge species. Phylogenetic analysis of sequence data from eukaryotic DGGE analysis revealed that the communities present in Antarctic sponges fell into diatom and dinoflagellate clusters with many sequences having no known close relatives. In addition, seven eukaryotic sequences that were not detected in seawater samples or other sponge species were observed in K. varialosa .

Drought tolerance of apple rootstocks: Production and partitioning of dry matter - Christopher J. Atkinson; Michaelangelo Policarpo; Anthony D. Webster; Ayzin M. Kuden (Plant and Soil, 1999)